Characteristics of Malaysian Chinese Primary Schools and Their Influence on Character Building - Ho, Nee Yong (AeU, 2015)
The paper focuses on the distinct characteristics in Malaysian Chinese primary schools and their influence on character building. The operational definition of ‘characteristics’ in this study are the eight independent variables namely: 1) Dong Jia Jiao (DJJ董家教), an abbreviation of School Boards of Governors (SBGs) and Parent-teacher Associations (PTAs), 2) Mother tongue education, 3) Trilingualism, 4) The thoughts of Confucianism and school discipline, 5) Teachers and Pedagogy, and 6) Environment at home and in school. The sole dependent variable is Character building of which the operational definition encompasses the eagerness to study, practising good values and having a sense of shame (Chen, 1966). The historical development, present condition, and future challenges of Chinese primary schools are discussed to give an overview of an education system that is unique not only in Malaysia but also to the world. The study design of this paper comprises of descriptive statistics, inferential statistics involving both the parametric and non-parametric methods, and triangulation statistics with qualitative data acquired from government documents and literature reviews. The 431 teachers from all over Malaysia who answered the questionnaires in full have agreed that there is close relationship between school characteristics and character building of pupils. The teachers and pedagogy stands out distinctively and its generous contributions and efforts towards the building of new classrooms instilled in the minds of pupils the virtue of self-sacrifices and the importance of paying back to society. The mother tongue education is of paramount importance to many parents because of the character building element in the school learning environment. The survey shows that the noble intention of the Chinese community in establishing mother-tongue primary schools has been initiated principally on Chinese community's efforts. They have to struggle for survival against constant controversies and obstacles as the country undergoes the changing political scenarios after each election. Trilingualism, however, has not been of much efficacy with 80% of the respondents saying that pupils generally could not master three languages well. This argument however is not true in elite city schools where majority of parents are professionals and speak English at home. The teaching of the thoughts of Confucianism has been found to be instructed subtly through stories of Chinese proverbs and idioms. The perception that Chinese primary schools are famed for being very strict in discipline has been proven to be true. Though the Ministry of Education has banned caning in class except by the authorised Senior Assistants and with witnesses, some teachers are vocal in disciplining their pupils. As more than 30% of teachers have indicated their desire to retire early, the effort in character building has been weakened by that much. The general perception that the pedagogy used in Chinese primary schools centres on 'spoon-feeding' method has not been indicated in the survey. Majority of teachers have agreed that character building must begin at home and continue in school. In conclusion, the survey confirms the close relationship between schools characteristics and character building of pupils in Chinese primary schools. The stakeholders in DJJ, schools and teachers have crystallised their goal in education as being the nurturing of pupils who are eager to learn, practise good values and have a sense of shame. These are the values expounded by Confucius education and are in consonant with the global objective of character education. The future research study on developing educational innovations towards character building, better national integration and racial harmony in Malaysia will be a vital research to pursue.